Extractable and Non-Extractable Antioxidants - Lucarini, Massimo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Special Issue "Extractable and Non-Extractable Antioxidants" gives an updated view on antioxidants-both in their extractable and non-extractable form-in the different food groups, their products thereof, and food preparations as well as byproducts and biomass waste. The potential beneficial properties of these compounds and nutraceutical formulations are described in the various studies covered in this Special Issue.